Role of Psychologists in Developing Mental Health and Professional Awareness among New Employees - Yahya, M., Khatabeh; Dhafer, M., Alqahtani; AHMED, S., ALAHMED; Ali, H., Alsuhibani (Migration Letters, 2023)
The study aimed to identify the role of psychologists in developing mental health and professional awareness among new employees and based on demographic differences. The study sample consisted of (N =556) new employees. Thay instrument included: The mental health scale (Vázquez-Colunga et al., 2017), and professional awareness scale (Ibrahim et al., 2014) which used to achieve the objectives of the study. The study found that the arithmetic averages of the mental health scale dimensions were high; the cognitive dimension had an average of 4.04, followed by the spiritual dimension (3.96) and the behavioral dimension 3.76. The role of psychologists in developing mental health and professional awareness among newly employed employees was statistically significant, as the value of t for all dimensions ranged from (27.576 to 36.739). The statistical significance of less than (0.05) was (0.000) for all dimensions of the mental and total health scale and the occupational awareness scale. Research indicates that mental health development significantly predicts professional awareness among newly employed employees (α =.05). Mental health development in its fields clarifies 14.4% of occupational awareness variation among newly employed employees.